Multicentric prospective study on computed tomography-guided periradicular infiltration and facet joint infiltration - Cantré, Daniel; Gerigk, Lars; Sprengel, Simon David; Plathow, Christian; Burkholder, Iris; Weber, Marc-André; Schedler, Anna; Rehnitz, Christoph (Neuroradiology, 2025)
Purpose Evaluation of the success of periradicular infiltration and facet joint infiltration in a multicenter and prospective approach. Materials and methods 114 patients undergoing therapeutic nerve root or facet joint infiltration for radicular and/or facet joint symptoms between the first lumbar and the first sacral segments were prospectively and consecutively enrolled across nine participating study centers in Germany. These centers provide CT-guided pain procedures continuously over a period of 96 months. Assessment was carried out by means of a systematic patient survey including pain questionnaires. The severity of the pain and the impairment caused by pain were assessed using 11-point Numerical Rating Scales. Results CT-guided periradicular infiltration and facet joint infiltration significantly reduced pain levels and substantially reduced pain frequency at all time points and up to three months after the last intervention. All pain related characteristics (i.e. actual pain, average pain level, maximum pain level) were significantly (95% confidence intervals (CI) ranging between − 1.0 and − 5.0) reduced at all time points when compared to the baseline. Besides the pure pain levels, the presented data also provide detailed insights into the complex associated issues the patient collective is facing including impairment in everyday life, fitness for work and leisure time activities. These parameters were also substantially improved (95% CI between − 0.0 and − 5.0) at all time points indicating a comprehensive patient benefit. Self-reported patient satisfaction, recommendation of the procedure and personal success were rated high (62-100%). The rate of patients on sick leave dropped from 23.7 to 1.9%. Accordingly, patients reported a high rate of satisfaction with the procedures. There was a high technical and clinical success rate with no major complications. Conclusion CT-guided pain therapy on the lumbar spine is effective and safe with a comprehensive benefit for patients, including not only pain levels in the narrow meaning but also regarding everyday life, fitness for work and leisure time activities at all investigated time points including 3 months follow-up.
Gesehen am 14.10.2025